2018
DOI: 10.4018/ijabim.2018010105
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Adoption of Sports Brand Apps

Abstract: The purpose of this article was to apply the modified technology acceptance model (TAM) to examine factors influencing consumers' intention and actual behavior in using sports brand apps. Convenience sampling was conducted for Korean consumers (N = 261) of sports brand apps. Data were analyzed by partial least squares structural equation modeling (PLS-SEM) using SmartPLS 3.0. The results found that the level of enjoyment had a significantly positive effect on the perceived ease of use, while perceived ease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 43 publications
3
58
0
5
Order By: Relevance
“…To test quality, risk of bias analysis of the 19 studies evaluated in the research showed that only three studies had a high score of 15 points or more out of 20 total [1,45,51], most studies (n = 14) had a mean score between 10 and 15 points and only two studies had a score below 10 points [52,53]. It should be noted that none of the studies analyzed carried out a calculation of the sampling required for the generalization of the results, which could be due to the fact that all the studies carried out a selection of the sample for convenience within a certain population.…”
Section: Analysis Of the Risk Of Bias In Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…To test quality, risk of bias analysis of the 19 studies evaluated in the research showed that only three studies had a high score of 15 points or more out of 20 total [1,45,51], most studies (n = 14) had a mean score between 10 and 15 points and only two studies had a score below 10 points [52,53]. It should be noted that none of the studies analyzed carried out a calculation of the sampling required for the generalization of the results, which could be due to the fact that all the studies carried out a selection of the sample for convenience within a certain population.…”
Section: Analysis Of the Risk Of Bias In Studiesmentioning
confidence: 99%
“…Analyzing the sample used in the different studies, there is a total of 16,025 subjects with an average sample of 843.42 subjects per study, with the Ndayizigamiye; Kante, and Shingwenyana study [54] having the smallest sample (n = 139) and Wei, Vinnikova, Lu and Xu study [55] having the largest sample with a total of 8840 subjects. Approximately a half of the studies (n = 8) used university students as a sample, followed by studies that considered users of sports applications (n = 4) and other studies took as their general population [54][55][56], a population of sports consumers [45], employees of a sports organization [57] and members of a fitness community [44,58]. Most studies had a higher proportion of females than males (n = 9), followed by studies that had parity in the sample (n = 5), four studies had a higher proportion of males while one study did not indicate the gender distribution of the sample [34].…”
Section: Summary Of Reported Intervention Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mobile Apps are pervasive lately and have permeated every aspect of our lives as a result of the proliferation of Smartphones which has made it easier for the development of these Apps (Statista, 2016). The Vodafone Group (2015, p. 211) and Byun et al (2018) defined Mobile Apps as software programs "designed to run on smartphones or tablet devices and provide a convenient means for the user to perform certain tasks". Also, Hoehle and Venkatesh (2015) in conceptualizing a Mobile Apps refers to it as "an IT software artifact that is specifically developed for mobile operating systems installed on handheld devices, such as smartphones or tablet computers".…”
Section: Literature Review 21 the Concept Of Mobile Appsmentioning
confidence: 99%